HARGA DIRI, EFIKASI DIRI, MOTIVASI BELAAR, DAN BERPRESTASI AKADEMIK SISWA SMA PADA BERBAGAI MODEL PEMBELAJARAN - Novariandhini, Dinda Ayu; Latifah, Melly (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This study aims was to analyze the self-esteem, self-efficacy, learning motivation, and academic achievement of high school students in various learning models that involved 26 students of the acceleration class, 30 students of the international class, and 30 students of the regular class in Bogor City. The third class represent each learning models in this research. Data was collected by self-report with the help of a questionnaire. The study using descriptive and inference analysis. The results found a different intrinsic motivation between students of the three learning models. The results also showed different evaluation results between students of the three classes that was accelerated class had the highest achievement of cognitive and psychomotor. The study also found a positive significant correlation between self-esteem with self-efficacy, intrinsic motivation, and extrinsic motivation. In addition, results found a positive significant correlation between self-efficacy with intrinsic motivation and extrinsic motivation. The results also showed a negative relationship between intrinsic motivation with cognitive and psychomotor achievement level of the students.